Marine science in Aotearoa New Zealand in 2050: a community-sourced over-the-horizon perspective - Thoral, Francois; Kaikkonen, Laura; O’Connor, Gabby; Russell, Pete; Dalinghaus, Charline; Rampal, Neelesh; Patchett, Laila; Robertson, Billie; Berdinner, Baxter; Robertson, Isla; et al. (New Zealand Science Review, 2025)
As natural and social environments continue to change, socioeconomic systems need to anticipate change and adequately react. Science, in general, is a critical component of the anticipation. Marine science, as a scientific research field that seeks to understand a significant proportion of our planet, is no exception. Here we provide an outlook on the future of marine science - how it is perceived by society and done by people – in Aotearoa New Zealand. This was informed by a group of early, mid, and late career marine scientists, industry representatives, Indigenous coastal guardians, high school students and ocean users who sought to envision what marine science could look like in 2050. Based on a workshop session, we provide ten recommendations to stakeholders, managers, funders, and scientists to bring marine science closer to a trajectory aligned with society’s expectations and needs. Marine science needs to adapt practices to respond to an increasing demand for providing both expert knowledge and public information, as well as addressing precarious working conditions and rising expectations to build a fairer, more inclusive, and just science system. Here we examine ways to involve a wide range of present and future actors to increase engagement, collaboration, diversity, impact and ultimately safeguard the worthiness of this research field in a fast-changing society.